2016
DOI: 10.1103/physrevd.93.125016
|View full text |Cite
|
Sign up to set email alerts
|

Scaling laws in chiral hydrodynamic turbulence

Abstract: We study the turbulent regime of chiral (magneto)hydrodynamics for charged and neutral matter with chirality imbalance. We find that the chiral magnetohydrodynamics for charged plasmas possesses a unique scaling symmetry, only without fluid helicity under the local charge neutrality. We also find a different type of unique scaling symmetry in the chiral hydrodynamics for neutral matter with fluid helicity in the inertial range. We show that these symmetries dictate the self-similar inverse cascade of the magne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
134
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(140 citation statements)
references
References 40 publications
5
134
1
Order By: Relevance
“…Recently, we have shown that the microscopic parity violation due to the left-handedness of neutrinos can drastically change the macroscopic hydrodynamic evolution of supernovae [1,2]. In particular, we pointed out that neutrino matter is topological and its topological nature is reflected in the hydrodynamic behavior of supernovae.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Recently, we have shown that the microscopic parity violation due to the left-handedness of neutrinos can drastically change the macroscopic hydrodynamic evolution of supernovae [1,2]. In particular, we pointed out that neutrino matter is topological and its topological nature is reflected in the hydrodynamic behavior of supernovae.…”
Section: Introductionmentioning
confidence: 87%
“…Recalling that the typical bulk fluid velocity is sufficiently small compared with the speed of light before and after the core bounce in supernovae, we expand the chiral hydrodynamic equations above in terms of v ≡ |v| as [1,2] …”
Section: Chiral Hydrodynamics For Neutrino Mattermentioning
confidence: 99%
See 2 more Smart Citations
“…It has been put forward by the present author that the microscopic parity violation due to the chirality of neutrinos must be reflected in the macroscopic evolution of supernovae [2,3]. Since parity is violated in the microscopic theory, parity must also be violated in the kinetic theory (and hydrodynamics if applicable) for left-handed neutrinos.…”
Section: Introductionmentioning
confidence: 99%